Analysis of vitality and biochemical parameters in freeze-thawed seminal plasma of rams - Cekić Bogdan; Kanzova Hristiyana; Petrov Georgi; Maksimović Nevena; Ćosić Ivan; Milovanović Aleksandar (Biotechnology in Animal Husbandry, 2022)
The current study aimed to examine the percentage changes of viability sperm and the activity of the enzymes LDH, ALP, GOT / AST, GPT / ALT in the sperm plasma of Lacaune rams, before and after cryopreservation. For this purpose, five rams were examined, and two ejaculates were obtained from each ram. Ejaculates are collected by the method of artificial vagina, during the insemination campaign. All ejaculates were diluted with a 6AG extender and frozen by the Cassou's sequin method. Sperm viability was determined by eosin and nigrosine smears, and enzyme activity was examined spectrophotometrically. As a result, the percentage of vital sperm after cryopreservation decreased by 15% (P ≤ 0.001). The freezing and thawing process also reduced the activity of the enzymes LDH, ALP, GOT / AST and GPT / ALP. In conclusion, the observed enzymes, in relation to sperm vitality, could be used as indicators to optimize the protocols for cryopreservation of ram's sperm.